Advances in the Noninvasive Diagnosis of Dry Eye Disease - Luca Di Cello (MDPI AG, 2021)
Dry eye disease (DED) is a multifactorial disease that represents one of the most common ophthalmologic conditions encountered in everyday clinical practice. Traditional diagnostic tests for DED, such as subjective questionnaires, tear film break-up time and the Schirmer test, are often associated with poor reproducibility and reliability, which make the diagnosis, follow-up, and management of the disease challenging. New advances in imaging technologies enable objective and reproducible measurements of DED parameters, thus making the diagnosis a multimodal imaging-based process. The aim of this review is to summarize all the current and emerging diagnostic tools available for the diagnosis and monitoring of DED, such as non-invasive tear breakup time, thermography, anterior segment optical coherence tomography, meibography, interferometry, in vivo confocal microscopy, and optical quality assessment. Although there is not a gold standard imaging technique, new multi-imaging-integrated devices are precious instruments to help clinicians to better cope with the diagnostic complexity of DED.